2015
DOI: 10.5812/jjm.20834
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis G Virus Among Hemodialysis and Kidney Transplant Patients in Khuzestan Province, Iran

Abstract: Background:Hepatitis G virus (HGV) is a member of Flaviviridae. Prevalence of HGV in healthy people is very low, but this virus is more prevalent in patients with hepatitis. Besides, relative frequency of HGV in patients undergoing hemodialysis, and kidney recipients is very high. The role of HGV in pathogenesis is not clear. Since this virus cannot be cultivated, molecular techniques such as Revers Transcription Polymerase Chain Reaction (RT-PCR) is applied to detect HGV.Objectives:The current study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Dadmanesh et al (2015) found that 4.3% of patients on HD were infected with HGV RNA in Tehran, which was lower than that obtained by the current study (30). Samarbaf-zadeh et al (2015) described that 3.14% of HD and kidney transplant patients had positive results for HGV RNA, which was lower than that obtained in the current study (19). Kargar Khaierabad et al…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Dadmanesh et al (2015) found that 4.3% of patients on HD were infected with HGV RNA in Tehran, which was lower than that obtained by the current study (30). Samarbaf-zadeh et al (2015) described that 3.14% of HD and kidney transplant patients had positive results for HGV RNA, which was lower than that obtained in the current study (19). Kargar Khaierabad et al…”
Section: Discussioncontrasting
confidence: 61%
“…Generally, the prevalence of HGV varies from 11% to 24%, among HCV-infected individuals (16)(17)(18). The prevalence of HGV infection varies in different regions of Iran and ranges from 3.14% to 10.73% (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence studies of HPgV-1 have been conducted among haemodialysis/renal disease patients in China, India, Indonesia, Iran, Japan, Nepal, Singapore, Taiwan, Thailand and Turkey 18,[93][94][95][96][97][98][99][103][104][105][106][107]114,115,117,152,[161][162][163][164][165][166][167][168][169][170][171][172][173][174] with rates >10% reported in China, 98,107 India, 117,161 Indonesia, 93,114 Iran, 169,172 Nepal, 97 Taiwan, 106,164 Thailand 95 and Turkey. 103,104,115,167,168…”
Section: Prevalence In Haemodialysis/renal Disease Patientsmentioning
confidence: 99%
“…Immune suppression is considered an important risk factor for BKV reactivation in CKD-HD patients. [56] Cardiovascular disease CVD is a common complication associated with both CKD and HD. It was reported that the burden of CVD in patients with long-term HD is increased by 5-10 folds compared with the general population.…”
Section: Other Viral Infectionsmentioning
confidence: 99%